Reduplikasi pada Novel Cantik Itu Luka Karya: Eka Kurniawan - Mesriana Marbun; Dardanila Dardanila; Amhar Kudadiri (Departement of Mathematics Education, 2024)
This research aims to describe the types of reduplication in the novel Cantik itu Luka by: Eka Kurniawan. This research is a descriptive qualitative research. The data source of this research is the novel Cantik itu Luka by: Eka Kurniawan. The data collection techniques used in this research are reading and note taking. The data is analyzed using Chaer's (2011) theory on the types of reduplication. The result of this study shows that there are 646 reduplication data in the novel Cantik itu Luka by: Eka Kurniawan. These 646 data are classified according to their types, namely 455 types of whole reduplication, 134 types of partial reduplication, 49 types of reduplication combined with affixes, and 8 types of reduplication with phoneme changes.